Literature review on COVID-19 vaccine efficacy in the immunocompromised population, and possible implications to future vaccination in kidney transplant patients - Park, Joo Kyung; Bhandari, Sunil (Frontiers in Medicine, 2023)
Since the emergence of the virulent coronavirus in 2019, efforts to tackle the coronavirus-disease-2019 (COVID-19) pandemic have been made globally. The development of the coronavirus disease (COVID) vaccine was a significant breakthrough in ways to tackle the virus. Various research studies have been conducted to identify how the virus works and ways to manage COVID, including the efficacy of the vaccines. However, there is limited data on how these measures work for the immunocompromised, despite the grave impact of these virulent strains in this population. Specifically, this review aims to focus on kidney transplant recipients (KTRs). Studies have suggested that there is significantly lower vaccine response in some immunocompromised groups despite additional booster doses, and hence warrants an augmented or alternative protection against the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) for these patients. This suggests a need for alternative or more tailored approach in providing adequate protection against the COVID-19 in these cohorts. Some suggested ways include withholding immunosuppressants before and/or after vaccination, increasing the vaccine doses or reducing intervals and providing a mixture of monoclonal antibody (mAb) or antiviral therapy. However, the appropriate degree of alteration and augmentation, as well as its safety and effectiveness remains to be determined. Furthermore, continuous emergence of more virulent strains, such as the Omicron and its sub-lineages or the Deltacron, emphasises the need for ongoing research to assess the effectiveness of the current treatment against these new variants. Overall, active interest and appropriate updates to COVID-19 guidelines is necessary.